2009
DOI: 10.1080/18811248.2007.9711508
|View full text |Cite
|
Sign up to set email alerts
|

Transmutation of126Sn in Spallation Targets of Accelerator-Driven Systems

Abstract: The practical feasibility of 126 Sn transmutation in spallation targets of accelerator-driven systems was evaluated from the viewpoints of accumulation of radioactive spallation products and neutron production as well as transmutation amount of 126 Sn. A cylindrical liquid 126 Sn target whose length depends on proton beam energy was described, based on a Pb-Bi target design of accelerator-driven system being developed in JAEA. A proton beam of 1.5 GeV-20 mA was estimated to give the transmutation rate of 126 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Guided by Xi Jinping's thought of socialism with Chinese characteristics in the new era, the integration of labor education and innovation and entrepreneurship education into the whole process of talent cultivation in colleges and universities in the new era has rich value implications for better implementing the fundamental task of establishing moral education, realizing all-round development of human beings, realizing high-quality entrepreneurship and employment of college students, and cultivating socialist builders and successors [4][5][6]. Under the great attention of the party and the state, all kinds of schools at all levels have gradually formed a good atmosphere of labor education, however, the lack of attention to labor education, the labor education system is not sound, and the related subjects have not formed a good synergy and other factors are superimposed to make the labor education in colleges and universities are still faced with cognitive dilemmas, systemic dilemmas, and path dilemmas, which highlight the necessity and urgency of constructing the mode of labor education in colleges and universities in the new era [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Guided by Xi Jinping's thought of socialism with Chinese characteristics in the new era, the integration of labor education and innovation and entrepreneurship education into the whole process of talent cultivation in colleges and universities in the new era has rich value implications for better implementing the fundamental task of establishing moral education, realizing all-round development of human beings, realizing high-quality entrepreneurship and employment of college students, and cultivating socialist builders and successors [4][5][6]. Under the great attention of the party and the state, all kinds of schools at all levels have gradually formed a good atmosphere of labor education, however, the lack of attention to labor education, the labor education system is not sound, and the related subjects have not formed a good synergy and other factors are superimposed to make the labor education in colleges and universities are still faced with cognitive dilemmas, systemic dilemmas, and path dilemmas, which highlight the necessity and urgency of constructing the mode of labor education in colleges and universities in the new era [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the study, it has been found that spallation reactions can be a solution to stabilizing 93 Zr. Han et al [12] investigate the transmutation of 126 Sn in the target of ADS.…”
Section: Introductionmentioning
confidence: 99%
“…A proposal to reduce the target activation is the use of low atomic mass targets, such as tin, in spite of the lower neutron yield of spallation in these materials. A further advantage of using tin spallation targets is that the ssion product Sn-126 can be introduced in them, thus contributing to the transmutation of this isotope [138,336].…”
Section: Technical Challenges Of Accelerator Driven Systemsmentioning
confidence: 99%